Proyectos de la Fundación para la promoción científica Edbertho Leal - Quiros de un observatorio astrofísico stellarium en Macaravita Santander (2023)
The Edbertho Leal Quirós Foundation for Scientific Promotion plans to build various infrastructures in the municipality of Macaravita (Santander) with the purpose of catalyzing the advancement of scientific research. This initiative is based on the exploitation of the favorable conditions that said municipality offers for astronomical observation. The planned projects include a Planetarium, an Astrophysical Observatory, an Environmental Laboratory, a Water Analysis Laboratory and a Flora and Fauna Laboratory, distributed in different areas within this Santander municipality.